2020
DOI: 10.1021/acs.jpcc.9b10889
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Determination of Bimetallic Particle Geometry: Suitability of Poorly Miscible Alloys for Surface-Enhanced Raman

Abstract: Bimetallic nanoparticles formed of poorly miscible alloys are attractive for applications in surface-enhanced Raman scattering (SERS), as they could allow the detection and study of analytes that do not bind well to typical plasmonic substrates, particularly important biomolecules such as serotonin. Despite their potential importance for SERS applications, the plasmonic and geometric properties of these alloys are not well characterized. Here, we present a method for calculating the thermodynamically minimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…CALPHAD neglects any surface or interfaces interaction between the phases, which are relevant at the nanoscale below 100 nm and are considered in the nano‐CALPHAD (Calculation of Phase Diagrams for nano‐systems) model by including an additional surface term to the Gibbs free energy of the system. This method is formally valid above the size threshold where surface topology and quantum effects become important, that is below 3–5 nm [92,93] …”
Section: Modellingmentioning
confidence: 99%
“…CALPHAD neglects any surface or interfaces interaction between the phases, which are relevant at the nanoscale below 100 nm and are considered in the nano‐CALPHAD (Calculation of Phase Diagrams for nano‐systems) model by including an additional surface term to the Gibbs free energy of the system. This method is formally valid above the size threshold where surface topology and quantum effects become important, that is below 3–5 nm [92,93] …”
Section: Modellingmentioning
confidence: 99%
“…New phenomena can be observed in nonequilibrium alloys, in addition to the additive properties of the distinct elements forming the NPs [1,2,9] . Bimetallic nanoparticles containing plasmonic and transition metals are promising for surface‐enhanced Raman scattering (SERS) of important biomolecules such as serotonin [10] . Magnetic‐plasmonic bimetallic systems have the ability to magnetically capture target analytes and separate them from the assay matrix, that is crucial for the detection of disease‐specific biomarkers in body fluids by spectroscopic methods such as SERS [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Then, they used the calculated Janus geometry of the AuNi and AgNi systems to explore the applicability of these particles for surface-enhanced Raman scattering. 234 Using first-principles calculations and nonadiabatic molecular dynamics. Yang demonstrated that the stacking SnS and GeSe Janus structures will exhibit an electric field and excellent photocatalytic performance for overall water splitting.…”
Section: Application Of Computational Simulationmentioning
confidence: 99%
“…They discovered the geometry of the particles as a function of metal content, from core–shell Janus to phase separation. Then, they used the calculated Janus geometry of the AuNi and AgNi systems to explore the applicability of these particles for surface-enhanced Raman scattering . Using first-principles calculations and nonadiabatic molecular dynamics.…”
Section: Application Of Computational Simulation In Janus Particles R...mentioning
confidence: 99%